2022
DOI: 10.3390/su14031288
|View full text |Cite
|
Sign up to set email alerts
|

Using Trophy Hunting to Save Wildlife Foraging Resources: A Case Study from Moyowosi-Kigosi Game Reserves, Tanzania

Abstract: Globally, the role of trophy hunting in wildlife conservation has been a topic of much debate. While various studies have focused on the financial contribution of trophy hunting towards wildlife conservation, little is known about whether hunting activities can protect wildlife forage resources. We examined the effect of illegal livestock grazing on wildlife habitat in operational and non-operational wildlife hunting blocks in Moyowosi-Kigosi Game Reserves (MKGR), Tanzania. We assessed whether the physical pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…On the positive side, (i) not only is Tanzania the only country holding single populations of over 50,000 buffalo, but there are three of these populations in the country; and (ii) several ecosystems show positive trends with growing buffalo populations, for example Serengeti Ecosystem. On a more worrying side, the overall national trend of buffalo is on the decrease due to (i) severe encroachment by livestock tending to replace buffalo in several ecosystems (Prins, 1992;Musika et al, 2021Musika et al, , 2022Prins and De Jong, 2022) and (ii) steady agricultural expansion and associated settlements.…”
Section: Tanzaniamentioning
confidence: 99%
“…On the positive side, (i) not only is Tanzania the only country holding single populations of over 50,000 buffalo, but there are three of these populations in the country; and (ii) several ecosystems show positive trends with growing buffalo populations, for example Serengeti Ecosystem. On a more worrying side, the overall national trend of buffalo is on the decrease due to (i) severe encroachment by livestock tending to replace buffalo in several ecosystems (Prins, 1992;Musika et al, 2021Musika et al, , 2022Prins and De Jong, 2022) and (ii) steady agricultural expansion and associated settlements.…”
Section: Tanzaniamentioning
confidence: 99%
“…For example, UK newspapers frequently assert that trophy hunters kill iconic animals and contribute to biodiversity decline, but seldom mention evidence that well-regulated, community-led trophy hunting can generate sustainable direct or indirect benefits for wildlife populations and for people who live in rural areas where livelihood options can be limited [13]. Documented benefits from well-regulated trophy hunting include employment in hunting and related industries, meat from hunted animals, and revenues that can defray substantial costs associated with wildlife conservation and support economic development, for example through investments in infrastructure, healthcare and education [14,[19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…However, the increasing illegal grazing inside MKGR affects forage resources for wildlife (Musika et al, 2021b). Also this study found there is high dietary overlap between buffalo and livestock (Kimuyu et al, 2017) warned that even a slight partial dietary overlap will affect the spatial use of wildlife.…”
Section: (Ii) Spatial Separation Between Buffalo and Livestock Increa...mentioning
confidence: 68%
“…Studies show that grazing reduces grass cover (Lu et al, 2017;Musika et al, 2022;Rahmanian et al, 2019), grass biomass (Shen et al, 2019), causes higher soil bulk density which in turn affects soil infiltration and penetration capacity (Musika et al, 2022;Shen et al, 2019). Grass cover protects soil, their roots increases soil aeration, their decomposition increases organic matter (Rahmanian et al, 2019), it reduces bulk density and enhances soil infiltration (Haruna et al, 2018).…”
Section: Impact Of Livestock Grazing On Essential Parameters Of Wildl...mentioning
confidence: 99%
See 1 more Smart Citation